PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN WORK LIFE BALANCE TERHADAP MOTIVASI GURU SEKOLAH MENENGAH PERTAMA KABUPATEN TORAJA UTARA - Silvani Majid Dendang; Arismunandar; Suardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of transformational leadership and work-life balance on the motivation of junior high school teachers in North Toraja Regency. This research was conducted because there were still teachers who experienced decreased work motivation, such as low participation in professional development activities and limited involvement in school programs. This study employed a quantitative approach using a survey method. The sample consisted of 168 junior high school teachers in North Toraja Regency selected through a total sampling technique. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was carried out using descriptive statistics and multiple linear regression with the assistance of SPSS version 25. The results showed that the principals’ transformational leadership and teachers’ work-life balance were categorized as good. Both variables had a positive and significant effect on teacher motivation, both partially and simultaneously. This means that the better the principals’ leadership and the teachers’ work-life balance, the higher the teachers’ motivation in carrying out their duties. The novelty of this study lies in examining the combined effect of transformational leadership and work-life balance on junior high school teachers’ motivation in North Toraja Regency, which has rarely been studied in the educational context of the region.